Observational study of the development and evaluation of a fertility preservation patient decision aid for teenage and adult women diagnosed with cancer: the Cancer, Fertility and Me research protocol. Issue 3 (13th March 2017) - Jones, G L; Hughes, J; Mahmoodi, N; Greenfield, D; Brauten-Smith, G; Skull, J; Gath, J; Yeomanson, D; Baskind, E; Snowden, J A; Jacques, R M; Velikova, G; et al.
Abstract : Introduction: Women diagnosed with cancer and facing potentially sterilising cancer treatment have to make time-pressured decisions regarding fertility preservation with specialist fertility services while undergoing treatment of their cancer with oncology services. Oncologists identify a need for resources enabling them to support women's fertility preservation decisions more effectively; women report wanting more specialist information to make these decisions. The overall aim of the 'Cancer, Fertility and Me' study is to develop and evaluate a new evidence-based patient decision aid (PtDA) for women with any cancer considering fertility preservation to address this unmet need. Methods and analysis: This is a prospective mixed-method observational study including women of reproductive age (16 years +) with a new diagnosis of any cancer across two regional cancer and fertility centres in Yorkshire, UK. The research involves three stages. In stage 1, the aim is to develop the PtDA using a systematic method of evidence synthesis and multidisciplinary expert review of current clinical practice and patient information. In stage 2, the aim is to assess the face validity of the PtDA. Feedback on its content and format will be ascertained using questionnaires and interviews with patients, user groups and key stakeholders. Finally, in stage 3 the acceptability of using this resource when integrated into usual cancer care pathways at the point of cancer diagnosis and treatment planning will be evaluated. This will involve a quantitative and qualitative evaluation of the PtDA in clinical practice. Measures chosen include using count data of the PtDAs administered in clinics and accessed online, decisional and patient-reported outcome measures and qualitative feedback. Quantitative data will be analysed using descriptive statistics, paired sample t-tests and CIs; interviews will be analysed using thematic analysis. Ethics and dissemination: Research Ethics Committee approval (Ref: 16/EM/0122) and Health Research Authority approval (Ref: 194751) has been granted. Findings will be published in open access peer-reviewed journals, presented at conferences for academic and health professional audiences, with feedback to health professionals and program managers. The Cancer, Fertility and Me patient decision aid (PtDA) will be disseminated via a diverse range of open-access media, study and charity websites, professional organisations and academic sources. External endorsement will be sought from the International Patient Decision Aid Standards (IPDAS) Collaboration inventory of PtDAs and other relevant professional organisations, for example, the British Fertility Society. Trial registration number: NCT02753296; pre-results.